Kinetic Study of Methyl Green Dye Adsorption from Aqueous Solution by Bauxite Clay at Different Temperatures - Abbas, Ahmed Mohammed; Abd, Suha Sahib; Himdan, Takialdin abdulhadi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Kinetic experiments were performed to induce of the green methyl dye adsorption from aqueous solution on the bauxite clay. This study includes determination of the adsorption capacity of bauxite clay to methyl green dye adsorption and study the effect of some parameters ( temperature , time ) on the kinetic of the adsorption process of the dye were studied. Quantity of dye adsorbed was increased when the temperature increases from 298 to 318K which indicates that methyl green adsorption processes are endothermic nature . In order to describe the kinetic data and the rate adsorption constants of the pseudo-first-order and second-order kinetics were used . The kinetics data were applied well with the second-order kinetic model. From activation energy value (Ea) for methyl green dye are energetically favorable and the dye adsorption includes physical and chemical adsorption types